The Impact of Brand Trust and Brand Image on Purchase Decision Through Buying Interest Consumers as an Intervening Variable - Prasetiyo, Dimas; Firdaus, Firdaus; Jumai, Jumai; Nurhayati, Nurhayati (Economics and Business International Conference Proceeding, 2024)
Wangta Agung or better known with Ardiles operating in the footwear sector in Indonesia. This research aims to analyze and describe impacts brand trust and brand image towards Purchase decisions through purchase interest consumers as an intervening variable. This research method uses distributing questionnaires to 100 respondents, with a non-sampling technique probability sample. Collection technique data using a Likert scale with distribute questionnaires via Google Form. The analysis method uses with SEM-PLS 4.0. The research results show that brand trust and brand image do not positive and non-significant effect, brand trust has a positive effect and significant impact on consumer buying interest the same as the brand image variable, the intervening variable buying interest has an influence positive towards purchasing decisions, Brand trust andbrand image have an influence positive and significant to the decision purchases through consumer buying interest as an intervening variable.It means with the presence of intervening variables will make consumers more interested and make purchasing decisions on Ardiles products in the city of Semarang